Intelligent Pyroptosis Inducer for Precise and Augmented Tumor Therapy Through Specific Activation Pyroptosis in Tumor - Linlin Huo; Shiqi Zhu; Muyao Li; Mingya Tan; Mengke Fan; Jiayi Zhao; Jie Zeng; Meiling Liu; Kunyan Liu; Chao Tong; Zhenghuan Zhao (Advanced Science)
Abstract Pyroptosis inducer, a powerful anti‐tumor agent that causes obvious programmed cell death and immune stimulation, has been challenged to trigger specific pyroptotic tumor cell death while keeping pyroptosis silence in normal cells. Here, an intelligent inducer is reported that acts as a reactive oxygen species (ROS) scavenger in normal cells to keep pyroptosis silence, while serving as ROS generator to induce obvious pyroptotic tumor cells death dependent on high hydrogen peroxide levels and near‐infrared laser irradiation. This switchable activity ensures this inducer to precisely kill the tumor cells with augmented immunogenicity while causing minimal damage to normal cells. Moreover, the catalase‐like activity endows this inducer to overcome limitation of tumor hypoxia on ROS generation and show significant pyroptosis activation, further initiating the immune response to inhibit the tumor metastases in vivo. This study provides valuable insights into design new pyroptosis inducer with controllable pyroptosis activity to specifically induce programmed tumor cell pyroptosis for precise and augmented tumor therapy with minimal side effects.